PEMBANGUNAN KARAKTER CINTA LINGKUNGAN MELALUI LITERASI LINGKUNGAN BERBASIS ECO-SCHOOL PROGRAM PADA ANAK USIA DINI - Pujiati, Amin; Saraswati, Sinta; Dwi Handayani, Bestari; Ismiyati, Ismiyati (Jurnal Abdi Insani, 2025)
This community service partnership was carried out at PAUD Mutiara Kids, Temanggung. PAUD Mutiara Kids faces two problems in its educational activities, namely 1) aspects of knowledge about waste and separating types of waste; 2) aspects of skills in making educational toys by utilizing used goods into more useful items so as to reduce waste at school. Therefore, the service team aims to (1) introduce and socialize the “Eco-school” program as an alternative to realizing environmental literacy in schools; (2) learning activities together to recognize and separate the types of waste are continued; (3) making educational toys from used items. Community service activities are carried out in socialization and demonstration activities, practice and assistance in sorting waste, discussions. This activity was carried out on Saturday, June 29, 2024 with 35 participants from Kindergarten B PAUD Mutiara Kids Temanggung. The results of this activity are 1) students gain knowledge about waste and can separate the types of waste; 2) students have the skills to utilize used items around the school into educational toys that can reduce waste at school; 3) students also said that this activity was very helpful to instill love for the environment for students. The Eco-school activities carried out are not only on theoretical understanding but also on application. Furthermore, this activity can be sustainable not only for Eco-school activities, but also for other activities that help school activities to be better.